2010
DOI: 10.1074/jbc.m110.156067
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Recognition of Nucleoside Triphosphate by Gene 4 Helicase of Bacteriophage T7

Abstract: The translocation of DNA helicases on single-stranded DNA and the unwinding of double-stranded DNA are fueled by the hydrolysis of nucleoside triphosphates (NTP). Although most helicases use ATP in these processes, the DNA helicase encoded by gene 4 of bacteriophage T7 uses dTTP most efficiently. To identify the structural requirements of the NTP, we determined the efficiency of DNA unwinding by T7 helicase using a variety of NTPs and their analogs. The 5-methyl group of thymine was critical for the efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…1b ). These results resolve the mystery of the apparent lack of significant unwinding activity seen in bulk studies 4 – 6 , 8 ; unwinding and slippage could not be separated, so unwinding was masked by unobservable slips that prevented helicase from moving over a substantial distance. The current work is the first direct observation of helicase nucleotide-specific slippage.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…1b ). These results resolve the mystery of the apparent lack of significant unwinding activity seen in bulk studies 4 – 6 , 8 ; unwinding and slippage could not be separated, so unwinding was masked by unobservable slips that prevented helicase from moving over a substantial distance. The current work is the first direct observation of helicase nucleotide-specific slippage.…”
mentioning
confidence: 53%
“…Despite the fact that most motor proteins use ATP as a fuel source, previous bulk studies have shown T7 helicase does not unwind DNA efficiently in the presence of ATP, although it is capable of ATP hydrolysis 5 , 6 , 8 . To investigate why ATP appeared not to support T7 helicase unwinding, we employed a single molecule optical trapping assay that we previously developed to measure unwinding of double-stranded DNA (dsDNA) or translocation on single-stranded DNA (ssDNA) ( Fig.…”
mentioning
confidence: 99%
“…Proteins were purified as previously described (12,19,36), with a slight modification in the case of gp4 detailed in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleotide hydrolysis is integral for helicase activity, however the nucleotide of choice can vary between unrelated or homologous proteins. T7 gp4, for example, hydrolyzes dTTP and dATP equivalently in the absence of DNA, but hydrolyzes dTTP threefold more when DNA is present [42]. Conversely, human Twinkle is less selective, but without the addition of DNA best hydrolyzes ATP and dATP [7].…”
Section: Discussionmentioning
confidence: 99%